Effects of polystyrene nanoplastic gestational exposure on mice. (May 2023) - Wang, Xiaoke; Zhao, Zixuan; Wang, Xin; Hu, Wenxuan; Chao luo; Chu, Xiuyu; Qian, Muzhou; Wang, Rui; Yu, Shali; Wu, Qiyun; Tang, Juan; Zhao, Xinyuan
Abstract: Airborne plastic particles have received increasing attention due to their ubiquity in the atmosphere and potential human health risks. Previous studies have demonstrated that early-life exposure to environmental toxicants is associated with abnormal metabolic function. However, the impact of exposure to polystyrene nanoplastics (PSNPs) through inhalation on the development of non-alcoholic fatty liver disease (NAFLD) in mothers and offspring remains unknown. In the present study, mice were gestationally exposed to PSNPs at different doses (0, 1, 5, and 25 μg μl −1 ) through inhalation to investigate health hazards to the dam at weaning and to adult offspring. Gestational exposure to PSNPs at high doses significantly induced hepatic steatosis in the dam and upregulated genes involved in de novo lipogenesis, fatty acids (FAs) uptake, and triacylglycerol (TG) synthesis in the monoacylglycerol acyltransferase pathway. Gestational exposure to high doses of PSNPs led to hepatic steatosis in adult female offspring but not male offspring, and expression levels of genes related to FAs uptake and TG synthesis in the glycerol 3-phosphate pathway were significantly elevated. Collectively, our data demonstrate that gestational exposure to airborne PSNPs induced different development processes of NAFLD in the dam and offspring, providing vital data about plastic particulate toxicology. Graphical abstract: Image 1 Highlights: Gestational exposure to PSNPs induced hepatic steatosis in dams. Gestational exposure to PSNPs programmed hepatic steatosis in female offspring. DNL, FAs uptake and MGAT pathway contributed to the hepatic steatosis in dams. FAs uptake and G3P pathway related to the hepatic steatosis in female offspring.